THE EFFECT OF BLENDED LEARNING (INDIVIDUAL ROTATE, FLEX, AND INSIDE-OUT) ON DIGITAL LITERACY SKILLS IN SCIENCE LEARNING - ana, Fitri; Adnan, Adnan; Azis, Andi Asmawati (JURNAL EDUSCIENCE, 2025)
Purpose - Applying a blended learning approach assisted by a Learning Management System (LMS) in science subjects can improve students' digital literacy skills. This study aims to investigate the effect of three types of blended learning, namely individual rotate, flex, and inside-out types, on students' digital literacy skills in science subjects.Methodology—The study used quantitative research with a pure experimental design (true experiment). The population in the study was all eighth-grade students, and the samples were four classes with a total of 124 students. The instrument used is a questionnaire that aims to assess the impact of blended learning implementation on students' digital literacy skills. The questionnaire was given before and after the application of blended learning.Findings - The results of data analysis show that the three types of blended learning affect digital literacy skills; this can be proven by the significance value of 0,001, which means that there is a significant difference in digital literacy skills between students taught with individual rotation, flex, and inside-out blended types. The three types of blended learning applied in the experimental class affected digital literacy skills. However, it is not significantly different as evidenced by the individual rotation, flex, and inside-out blended learning types at Sig> 0,05 level.Contribution—This research shows that blended learning can be a solution in education for learners and educators who utilize internet-based technology in the learning process. However, improvements in the provision of internet facilities are still needed to overcome the existing challenges.